ANALISIS FAKTOR YANG MEMPENGARUHI PELAKSANAAN PROGRAM TRIAS USAHA KESEHATAN SEKOLAH (UKS) DI SLB C BANTUL - Rahmah Widyaningrum (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2016)
School Health Program is one of the principal program of Public Health Center with students as the main target. The principle of healthy living and health status of students had not been as expected. This was evident from health problems of students include the emergence of diarrheal diseases, intestinal worms, and dental caries. The Objective of study is to obtain an overview of the implementation of the School Health Program at Special Education Settings in Bantul. The research was using qualitative methods with case study approach. The participants in the research are the principal, managers of School Health Program, and students of Dharma Bhakti Piyungan’s Special Education Setting and Bangun Putra Kasihan’s Special Education Setting, administrator of Piyungan and Kasihan I Public Health Center, administrator of the Steering Committee for subdistrict’s School Health Program, Health Office of Bantul Regency, and the Ministry of Youth and Sports of Yogyakarta Provincial. The qualitative data were collected with indepth interviews, observation, and documentation study. Analysis data was using interactive models of Huberman and Miles that included data reduction, data presentation, and conclusion, using the Open Code software version 3.6.2.0. The program’s implementation of School Health Program in Special Education Settings was good. In both Special Education Settings. School health program implementation constraints are cognitive limitation of students, teacher training and school coverage were minimal, economy condition and attitude of parents, lack of school readiness, and the involvement of relevant agencies. Factors that affected the implementation of School Health Program are curriculum, organization of school and partnerships. The implementation of the School Health Program Bantul’s Special Education Settings could be improved through the optimization of partnerships with Public Health Center, relevant authorities, Non Governmental Organizations, and College of Education and Health.